Gynecologic postoperative anti-adhesion barriers: From biomaterials to barrier development - Abbas Fazel Anvari-Yazdi; Daniel J. MacPhee; Ildiko Badea; Xiongbiao Chen (Biomaterials and Biosystems)
Gynecologic postoperative adhesions (GPOA) remain an under-appreciated source of morbidity despite advances in minimally invasive surgery. Adhesions forming after myomectomy, extensive endometriosis excision, repeat caesarean section, or hysteroscopic adhesiolysis develop in 20 – 90 % of patients and account for up to 40 % of secondary infertility, chronic pelvic pain, bowel obstruction, and life-threatening obstetric complications such as placenta accreta spectrum. Because the uterus is hormonally responsive and destined for potential pregnancy, anti-adhesion barriers for gynecologic tissues must meet stricter criteria for biocompatibility, resorption timing, teratogenic safety, and reproductive regulatory classification than barriers designed for bowel or tendon repair.This review consolidates the rapidly expanding literature on biomaterial-based barriers specifically tailored for gynecologic applications. We first dissect the pathophysiology of uterine and adnexal adhesion formation—including mesothelial disruption, fibrin persistence, and estrogen-modulated wound remodeling—to highlight design targets unique to the female reproductive tract. Next, we critically appraise natural and synthetic polymers, discussing how formulation parameters govern in-vivo elimination or excretion routes and influence fertility outcomes. Cutting-edge fabrication strategies—such as electrospinning, 3D bioprinting, melt electrowriting, Janus hydrogels, and microneedle patches—are reviewed with an eye toward uterine conformity, minimally invasive deployability, and on-demand release of drugs or exosomes. We further map current FDA-cleared films (INTERCEED™, Seprafilm®, SurgiWrap®) against unmet gynecologic needs, delineate limitations, and identify opportunities for multifunctional, self-healing, image-visible, and patient-specific barrier platforms.By framing adhesion prevention through a gynecologic lens, this article provides clinicians, materials scientists, and device developers with a roadmap for translating next-generation barriers from bench to bedside, ultimately reducing infertility, surgical re-admission, and obstetric risk in women worldwide.